Insulin resistance reduces arterial prostacyclin synthase and eNOS activities by increasing endothelial fatty acid oxidation - Du, Xueliang (American Society for Clinical Investigation, 2006)
Insulin resistance markedly increases cardiovascular disease risk in people with normal glucose tolerance, even after adjustment for known risk factors such as LDL, triglycerides, HDL, and systolic blood pressure. In this report, we show that increased oxidation of FFAs in aortic endothelial cells without added insulin causes increased production of superoxide by the mitochondrial electron transport chain. FFA-induced overproduction of superoxide activated a variety of proinflammatory signals previously implicated in hyperglycemia-induced vascular damage and inactivated 2 important antiatherogenic enzymes, prostacyclin synthase and eNOS. In 2 nondiabetic rodent models — insulin-resistant, obese Zucker (fa/fa) rats and high-fat diet–induced insulin-resistant mice — inactivation of prostacyclin synthase and eNOS was prevented by inhibition of FFA release from adipose tissue; by inhibition of the rate-limiting enzyme for fatty acid oxidation in mitochondria, carnitine palmitoyltransferase I; and by reduction of superoxide levels. These studies identify what we believe to be a novel mechanism contributing to the accelerated atherogenesis and increased cardiovascular disease risk occurring in people with insulin resistance.